Ultrastructural evaluation following catheterization of the fallopian tube with a hysteroscopic catheter - Kitamura, S. (Springer US, 1998)
PURPOSE: Our purpose was to assess the morphology and ultrastructural changes in the tubal epithelium following catheterization of the fallopian tube. METHODS: Fallopian tubes were obtained from 20 women who had undergone hysterectomies. Catheterization was performed in 20 tubes using a catheter developed for hysteroscopic tubal embryo transfer. The catheter has a — French diameter, tapering to 2 French (0.66 mm) at the tip portion. The 20 contralateral tubes served as controls and were not catheterized. Ultrastructural changes were examined by scanning electron microscopy and transmission electron microscopy. RESULTS: Scanning electron microscopy showed no transformation or defects of the tubal epithelium surface in catheterized or control tubes. Transmission electron microscopy showed no significant differences in the percentage of abnormal desmosomes and the percentage of basement membrane in ciliated and nonciliated cells between catheterized and noncatheterized tubes. No transformation or defects were observed in catheterized or noncatheterized tubes. CONCLUSIONS: These findings suggest that catheterization of the tube using a hysteroscopic catheter caused no acute damage to the tubal epithelium.